Structure and Properties of Alloys Obtained by Aluminothermic Reduction of Deep-Sea Nodules - Pavel Novák (Materials, 2021)
This paper brings an innovative processing route of manganese deep-sea nodules, which results in completely new grades of alloys. Deep-sea nodules were processed by aluminothermic method without the extraction of individual elements, producing complexly alloyed manganese-based “natural alloys”. Three levels of the amount of aluminum were used for the aluminothermic reduction, and hence the alloys differ strongly in the amount of aluminum, which has a significant effect on their phase composition. The alloys have very high wear resistance, comparable with tool steel. The disadvantage of low-aluminum alloy is the susceptibility to local thermal cracking during friction, which occurs especially in the case of a dry sliding wear against the static partner with low thermal conductivity.